Prognostic value of calcific aortic stenosis in patients of the PROGNOZ IBS registry - S. N. Tolpygina; A. V. Zagrebelny; S. Yu. Martsevich (Российский кардиологический журнал)
Aim. To assess the impact of calcific aortic stenosis on long-term prognosis in patients with stable coronary artery disease (CAD) included in the PROGNOZ IBS registry.Material and methods. The analysis included data of patients (n=541; men, 432; women, 109) from the CHD PROGNOSIS registry, in whom diagnosis of CAD was confirmed using coronary angiography during reference hospitalization in the National Medical Research Center for the period from January 1, to December 31, 2007. The mean age of men was 57,5±0,4, women — 60,9±0,9 years. The survival analysis included 504 patients (93%). The mean follow-up period was 7,3±2,19 years. We assessed the presence of calcific aortic stenosis (CAS) according to echocardiography and data on endpoints after 4 and 7 years of follow-up.Results. CAS according to echocardiography during reference hospitalization was found in 29 patients (5,4%) with a confirmed CAD. After four-year followup, 7 patients (24,1%) died, after 7 years — 15 (51,7%). Fatal and non-fatal cardiovascular events (primary endpoint) after 4 years were revealed in 10 patients (34,5%), and after 7 years, all cardiovascular events were fatal (n=15; 51,7%). In the presence of aortic stenosis, the relative risk (RR) of all-cause death at 4-year follow-up increased by 2,9 times (p<0,01), while at 7-year follow-up — by 3,2 (p<0,0001). The RR for the primary endpoint at 4-year follow-up increased by 2,8 times (p<0,01), while at 7-year follow-up — by 2,3 times (p<0,001). The RR of death in CAS patients at 7-year follow-up was comparable to severe heart failure — 3,3 (p<0,01), stroke — 2,4 (p<0,05) and left main coronary artery stenosis — 2,5 (p<0,0001).Conclusion. The presence of calcific aortic stenosis had a pronounced negative effect on the long-term prognosis of CAD patients, comparable with those in left main coronary artery stenosis, severe heart failure and stroke.